A framework convention on global health : a tool for empowering the HIV/AID movements in South Africa and Senegal - Dioh, Adrian (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.